The Modality-Specific Learning Style Hypothesis: A Mini-Review - Aslaksen, Karoline; Lorås, Håvard (Frontiers in Psychology, 2018)
The impact on learning outcome by tailoring instruction and teaching towards modality-specific learning style preferences has been research and debated for decades. Several topical reviews have concluded that there are no evidence to support this so-called meshing hypothesis, and that it represents a persistent neuromyth in education. The concept, however, is still utilized in educational practice and favored by many academics. This mini-review present literature in relation to the meshing hypothesis, which has applied explicit and rigorous methodological criteria. In order to demonstrate evidence for the meshing hypothesis, studies needed to screen participants for preferred learning style, assign participants to matched or non-matched conditions, provide the same test of learning for all participants, as well as present statistical crossover-interaction effects. Across studies that have applied these methodological criteria, the overall effect sizes was very low and non-significant, indicating still no replicable statistical evidence for enhanced learning outcome by matching instruction with modality-specific learning styles.